Twelve‐month outcomes of a bioabsorbable implant for in‐office treatment of dynamic nasal valve collapse. (28th June 2019) - Sidle, Douglas M.; Stolovitzky, Pablo; Ow, Randall A.; Silvers, Stacey; Matheny, Keith; Bikhazi, Nadim; Wani, Manish; Scurry, W. Cooper; Most, Sam P.
Abstract : Objectives: To examine 12‐month outcomes for in‐office treatment of dynamic nasal valve collapse (NVC) with a bioabsorbable implant. Study Design: Prospective, multicenter, nonrandomized study. Methods: One hundred sixty‐six patients with severe‐to‐extreme class of Nasal Obstruction Symptom Evaluation (NOSE) scores were enrolled at 16 U.S. clinics (November 2016–July 2017). Patients were treated with a bioabsorbable implant (Latera, Spirox Inc., Redwood City, CA) to support the lateral wall, with or without concurrent inferior turbinate reduction (ITR), in an office setting. NOSE scores and Visual Analog Scale (VAS) were measured at baseline and 1, 3, 6, and 12 months postoperatively. The Lateral Wall Insufficiency (LWI) score was determined by independent physicians observing the lateral wall motion video. Results: One hundred five patients were treated with implant alone, whereas 61 had implant + ITR. Thirty‐one patients reported 41 adverse events, all of which resolved with no clinical sequelae. Patients showed significant reduction in NOSE scores throughout 12 months postoperatively (77.4 ± 13.4 baseline vs. 36.2 ± 22.7 at 1 month postoperatively, 33.0 ± 23.4 at 3 months, 32.1 ± 24.6 at 6 months, and 30.3 ± 24.3 at 12 months; P < 0.001). They also showed significant reduction in VAS scores postoperatively (69.7 ± 18.1 baseline vs. 31.3 ± 27.1 at 12 months postoperatively, P < 0.001). These results were similar in patients treated with implant alone and those treated with the implant + ITR. Consistent with patient‐reported outcomes, postoperative LWI scores were demonstrably lower (1.42 ± 0.09 and 0.93 ± 0.08 pre‐ and postoperatively, P < 0.001). Conclusion: In‐office treatment of dynamic NVC with a bioabsorbable implant improves clinical evidence of LWI at 6 months and improves nasal obstructive symptoms in a majority of patients up to 12 months. Level of Evidence: 2b Laryngoscope, 130:1132–1137, 2020